Building A Comprehensive Customer Satisfaction Model In Retail Business: A Conceptual Approach - Putu Laksmita Dewi Rahmayanti; I Wayan Suartina; Nyoman Surya Wijaya; Miko Andi Wardana; Komang Sumerta (Enrichment : Journal of Management, 2022)
The purpose of this study is to build a comprehensive model of customer satisfaction. This research is an exploratory research through literature review. The analysis of the existing literature leads to the formulation of eight (8) research hypotheses. The findings of this study indicate that customer satisfaction is determined by product quality, service quality, perceived price fairness, promotion, distribution, brand image, attitudes, and customer experience. This research integrates in one conceptual model various variables that affect customer satisfaction which were previously studied separately. The influence and interaction of all the variables studied can explain what variables determine customer satisfaction. The results of the research in the form of a new comprehensive conceptual model can also be used as a consideration for retail businesses in increasing customer satisfaction.